An Experimental Study on the Effects of Air Humidity on the Spontaneous Combustion Characteristics of Coal. Issue 12 (2nd December 2017) - Ma, Dong; Qin, Botao; Song, Shuang; Liang, HongJun; Gao, Ang
ABSTRACT: This study evaluated the effects of air humidity on the spontaneous combustion characteristics of coal. Four levels of air relative humidity (dry air, 30%, 60%, and 100%) were used as the experimental air flow. The crossing point temperature (CPT) and oxidation products were measured using a self-designed spontaneous combustion system. We found CPT values of 153°C, 151°C, 150°C, and 148°C for the four levels of air humidity, respectively. The concentration of oxidation production increased with an increase in air humidity. Then, the thermal characteristics of coal were studied using the thermogravimetric and differential scanning calorimetric methods. It was found that a peak temperature II appeared at 417.28°C, 411.25°C, 402.64°C, and 385.68°C for the four air humidities, respectively. As a consequence, the adsorbed water had pushed the coal oxidation into the next stage.